Designing polymeric microparticles for biomedical and industrial applications - Campos, Elisa (2013)
Nowadays, there are almost limitless applications for microparticles. Microparticles are used as components in many advanced materials and composites, in the healthcare and personal grooming industries, and in many research and development applications. This review presents an overview of recent and current studies carried out at the Particles, Polymers and Biomaterials Technology Group of the University of Coimbra which aims to design and prepare novel polymeric microparticles. Microparticles herein described were prepared from natural polymers, namely, polyhydroxyalkanoates, cellulose, starch, and chitosan and from synthetic polymers, namely polyurethanes, poly(vinyl chloride), silanes, and methacrylates. These studies intended different applications for microparticles, mostly as delivery systems and coatings. The results of our studies confirm the outstanding potential of microparticles in different fields, and emphasize the importance of these systems for the future.